Any Guarantees? China's Rural Minimum Living Standard Guarantee Program - Golan, Jennifer (World Bank Group, Washington, DC, 2014)
This paper examines China's rural minimum living standard guarantee (dibao) program, one of the largest targeted transfer schemes in the world. Using household survey data matched with published administrative data, the authors provide background on the patterns of inequality and poverty in rural China, describe the dibao program, estimate the program's impact on poverty, and carry out targeting analysis. The authors find that the program provides sufficient income to poor beneficiaries but does not substantially reduce the overall level of poverty, in part because the number of beneficiaries is small relative to the number of poor. Conventional targeting analysis reveals rather large inclusionary and exclusionary targeting errors; propensity score targeting analysis yields smaller but still large targeting errors. Simulations of possible reforms to the dibao program indicate that expanding coverage can potentially yield greater poverty reduction than increasing transfer amounts. In addition, replacing locally diverse dibao lines with a nationally uniform dibao threshold can in theory reduce poverty. The potential gains in poverty reduction, however, depend on the effectiveness of targeting.